2020
DOI: 10.1364/oe.410385
|View full text |Cite
|
Sign up to set email alerts
|

Flexible GaAs photodetector arrays hetero-epitaxially grown on GaP/Si for a low-cost III-V wearable photonics platform

Abstract: We demonstrate flexible GaAs photodetector arrays that were hetero-epitaxially grown on a Si wafer for a new cost-effective and reliable wearable optoelectronics platform. A high crystalline quality GaAs layer was transferred onto a flexible foreign substrate and excellent retention of device performance was demonstrated by measuring the optical responsivities and dark currents. Optical simulation proves that the metal stacks used for wafer bonding serve as a back-reflector and enhance GaAs photodetector respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Even at low open-circuit voltage, Sample A showed a comparable conversion efficiency of 10.6%, which was slightly smaller than that of the upright cell on GaAs. Moreover, the short-circuit current was increased from 12.1 mA/cm 2 to 19.3 mA/cm 2 , probably due to the light-trapping effect and slight anti-reflection effect of the lift-off etching surface [13,30,31].…”
Section: Device Fabrication and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Even at low open-circuit voltage, Sample A showed a comparable conversion efficiency of 10.6%, which was slightly smaller than that of the upright cell on GaAs. Moreover, the short-circuit current was increased from 12.1 mA/cm 2 to 19.3 mA/cm 2 , probably due to the light-trapping effect and slight anti-reflection effect of the lift-off etching surface [13,30,31].…”
Section: Device Fabrication and Performancementioning
confidence: 99%
“…Growth of III-V materials on Si, however, creates several hurdles to overcome, such as large lattice mismatch, polar/non-polar growth, and thermal cracks [12][13][14][15][16]. The large lattice mismatch issue can be mitigated via dislocation filter layers, thermal cycle annealing, and two-step growth, while the polarity mismatch can be addressed by using an offcut Si wafer [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Gallium arsenide (GaAs) is a frequently used III-V semiconductor material that can be used as an alternative to Si-based materials based on its excellent charge-carrier mobility and high stability. Hong et al demonstrated a GaAs-based flexible photodetector array that was hetero-epitaxially grown on a Si wafer [56]. This innovative manufacturing method showed promising results that could lower the cost of inorganic photodiodes, which are normally expensive.…”
Section: Materials For Flexible Ppg Devicesmentioning
confidence: 99%
“…Beyond military and industrial applications, the importance of infrared photodetectors (PDs) is rapidly increasing with the emergence of advanced imaging systems in biomedical and wearable applications. However, since most of the PDs hitherto developed are implemented on rigid substrates, their applications are highly restricted. Mechanically flexible infrared PDs can overcome these limitations through the capability to adjust the curvature and geometries on different demands. , This will enable ultrathin and lightweight design, excellent implantability, and convenient portability, making them suitable for next-generation thermographic imaging sensors that can be incorporated for biomedical sensing and wearable health monitoring devices. …”
Section: Introductionmentioning
confidence: 99%
“…Organic-based semiconducting materials have been extensively studied for flexible PDs due to their intrinsic material property. However, organic-based PDs still showed lower efficiency, inferior reliability, and slow operation speed compared to inorganic semiconductor-based PDs. , In contrast, epitaxial lift-off (ELO) of III–V compound semiconductor thin films enabled flexible and reliable optoelectronic devices such as flexible GaAs solar cells and lasers. , To date, previous flexible III–V PD works have been performed for only “visible” and “near-infrared” wavelengths using the lattice-matched GaAs/AlAs on GaAs wafer or InGaAs/InAlAs on InP wafer, , but no studies have been reported in the mid-wavelength (3–5 μm) infrared spectral region mainly due to the difficulties of heteroepitaxial growth and ELO process of low-band-gap materials. For example, the heteroepitaxial growth of InAs ( E g = 0.36 eV) or InSb ( E g = 0.17 eV) on GaAs suffers from the extremely large lattice mismatch to GaAs, ∼7.2 and 14.6%, and this results in high threading dislocation density (TDD).…”
Section: Introductionmentioning
confidence: 99%